Lipid and Peptide-Oligonucleotide Conjugates for Therapeutic Purposes: From Simple Hybrids to Complex Multifunctional Assemblies - Fàbrega, Carme (2023)
Antisense and small interfering RNA (siRNA) oligonucleotides have been recognized as powerful therapeutic compounds for targeting mRNAs and inducing their degradation. However, a major obstacle is that unmodified oligonucleotides are not readily taken up into tissues and are susceptible to degradation by nucleases. For these reasons, the design and preparation of modified DNA/RNA derivatives with better stability and an ability to be produced at large scale with enhanced uptake properties is of vital importance to improve current limitations. In the present study, we review the conjugation of oligonucleotides with lipids and peptides in order to produce oligonucleotide conjugates for therapeutics aiming to develop novel compounds with favorable pharmacokinetics.